2005
DOI: 10.1080/14786410412331299005
|View full text |Cite
|
Sign up to set email alerts
|

Camptothecin and its analogues: a review on their chemotherapeutic potential

Abstract: Topoisomerase I (Topo-I) is a major target for anticancer drug discovery and design. As a result, Topo-I inhibitors constitute an important class of the current anticancer drugs. To date, all of the Topo-I inhibitors that have been clinically evaluated are analogues of camptothecin (CPT), an extract of the Chinese tree Camptotheca acuminata. CPT has shown significant antitumor activity to lung, ovarian, breast, pancreas and stomach cancers. In this article the, phytochemical aspect, and various structural modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 74 publications
0
86
0
Order By: Relevance
“…It is usually classified in the tupelo family Nyssaceae, which includes two species: Camptotheca acuminata Decne and Camptotheca lowreyana. Camptotheca acuminata has been used as traditionally Chinese medicine for centuries, all parts of this fast growing tree contain the secondary metabolite, camptothecin (CPT, an indole alkaloid), which is an effective drug against several types of cancer [2][3][4] . It is reported that CPT can induce apoptosis or death in various cancer cells by interfering with the topoisomerase I, an essential enzyme in the DNA replication process [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…It is usually classified in the tupelo family Nyssaceae, which includes two species: Camptotheca acuminata Decne and Camptotheca lowreyana. Camptotheca acuminata has been used as traditionally Chinese medicine for centuries, all parts of this fast growing tree contain the secondary metabolite, camptothecin (CPT, an indole alkaloid), which is an effective drug against several types of cancer [2][3][4] . It is reported that CPT can induce apoptosis or death in various cancer cells by interfering with the topoisomerase I, an essential enzyme in the DNA replication process [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Many of these novel anticancer agents have a history of use in traditional medicine, notably in TCM. The most prominent among them are: i) camptothecin, isolated from the Chinese 'happy tree' Camptotheca acuminata (19); ii) podophyllotoxin from Podophyllum peltatum, originally used by Native Americans but also found in large amounts in Podophyllum emodi var. Chinense (20); and iii) paclitaxel initially obtained from Taxus brevifolia and present in high quantities in Taxus chinensis (21).…”
Section: Discussionmentioning
confidence: 99%
“…Among others, two water soluble analogues of the alkaloid camptothecin are increasingly in clinical use [167][168][169][170]. Like many other pharmaceutical drug candidates, camptothecins have suboptimal properties mostly caused by their low water solubility and this resulted in their failure in early clinical trials [167].…”
Section: Methodsmentioning
confidence: 99%